Sounding native: rating speakers of English from Asia. Issue 3 (2nd September 2019) - Hansen Edwards, Jette G.
Abstract: This study explores whether a shift is taking place in terms of how the native speaker construct is viewed in relation to Asian Englishes. It investigates this issue through a speech ratings task. The goal of the current research is not to judge nativeness or ultimate attainment of the participants. Rather, the study investigates whether the construct of native speaker is being redefined as new varieties of English are gaining acceptance as legitimate varieties of English. The study comprises ratings of speech samples from 33 native speakers of English from Asia and 7 native speakers of English from Inner Circle countries. A total of 45 listeners rated each sample for nativeness on a 9-point Likert scale. The study also examined how listeners' perceptions of where the speaker was from and which the variety they felt the speaker spoke influenced ratings, as well as how the listeners' own backgrounds influenced ratings.